Recent developments in CE and CEC of peptides - Kasicka, Václav (Electrophoresis, 2008)
The article brings a comprehensive survey of recent developments and applications of high-performance capillary electromigration methods, zone electrophoresis, ITP, IEF, affinity electrophoresis, EKC, and electrochromatography, to analysis, preparation, and physicochemical characterization of peptides. New approaches to the theoretical description and experimental verification of electromigration behavior of peptides and to methodology of their separations, such as sample preparation, adsorption suppression, and detection, are presented. Novel developments in individual CE and CEC modes are shown and several types of their applications to peptide analysis are presented: conventional qualitative and quantitative analysis, purity control, determination in biomatrices, monitoring of chemical and enzymatical reactions and physical changes, amino acid and sequence analysis, and peptide mapping of proteins. Some examples of micropreparative peptide separations are given and capabilities of CE and CEC techniques to provide important physicochemical characteristics of peptides are demonstrated.
Keywords: Animals; Capillary Electrochromatography; lidé; peptidy; zvířata; Electrophoresis, Capillary; Peptides; kapilární elektrochromatografie; elektroforéza kapilární; Humans